2012
DOI: 10.2319/021712-149.1
|View full text |Cite
|
Sign up to set email alerts
|

Dental anomalies and clinical features in patients with maxillary canine impaction

Abstract: Objective: To analyze the prevalence, distribution, clinical features, and relationship with dental anomalies of maxillary canine impaction. Materials and Methods: The complete pretreatment records of 1674 orthodontic patients were examined. Subjects with maxillary impacted canines were divided into two study groups: a palatally displaced canine (PDC) group (114 patients) and a buccally displaced canine (BDC) group (37 patients). These were compared to a control group of 151 patients who were randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 26 publications
4
43
0
1
Order By: Relevance
“…This coincides with previous reports [9, 10, 12], although most of these studies only evaluated palatally displaced canines. However, in a study of Chinese patients exhibiting palatally and lingually displaced IMC, other DAs were associated.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This coincides with previous reports [9, 10, 12], although most of these studies only evaluated palatally displaced canines. However, in a study of Chinese patients exhibiting palatally and lingually displaced IMC, other DAs were associated.…”
Section: Discussionsupporting
confidence: 91%
“…The 6.04% IMC prevalence in the cohort is within the 1.73 to 9.02% interval reported in other populations [69, 11, 19, 20]; the 5.43% rate reported in Hungary is the closest to our study [20]. Bilateral impaction was present in 25% of the IMC patients—this is similar to the 19.2% observed in the Greek population [6].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…An investigation of the associated dental anomalies of the two types of impaction showed that both PDCs and BDCs were associated only with tooth agenesis. 9 Among BDCs, only those related to noncrowding have been associated with anomalous lateral incisors. 39 These findings may imply that, although PDCs and BDCs differ in their etiologic background, in the case of concurrent agenesis, some similarities can be expected.…”
Section: Maxillary Canine Impaction and Agenesis Statusmentioning
confidence: 99%
“…5,6 The prevalence of impaction appears to be higher in females compared to males, with the reported ratio ranging from 1.3:1 to 3.2:1 7,8 ; however, no evidence of an association between gender and canine location (labial/palatal) has been reported. 9 Maxillary canine impaction (MCI) occurs frequently together with other dental anomalies, such as second premolar agenesis, microdontia of maxillary lateral incisors, enamel hypoplasia, and infraocclusion of deciduous molars. 10 Other dental anomalies associated with MCI are missing and/or peg-shaped maxillary lateral incisors, [11][12][13][14] third molar agenesis, 13 generalized or localized tooth-size reduction, 7,11,12,15 distoangulation of unerupted mandibular second premolars, 16,17 generalized or localized delayed tooth development and eruption, 17 and transpositions.…”
Section: Introductionmentioning
confidence: 99%